2013
DOI: 10.1080/10508422.2012.714246
|View full text |Cite
|
Sign up to set email alerts
|

Threats to Moral Identity: Testing the Effects of Incentives and Consequences of One's Actions on Moral Cleansing

Abstract: Individuals engage in moral cleansing, a compensatory process to reaffirm one’s moral identity, when one’s moral self-concept is threatened. However, too much moral cleansing can license individuals to engage in future unethical acts. This study examined the effects of incentives and consequences of one’s actions on cheating behavior and moral cleansing. Results found that incentives and consequences interacted such that unethical thoughts were especially threatening, resulting in more moral cleansing, when la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…In support of this rationale, Harkrider et al . () found that prior transgressions motivated participants to act prosocially in order to repair negative feelings of moral self‐worth.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this rationale, Harkrider et al . () found that prior transgressions motivated participants to act prosocially in order to repair negative feelings of moral self‐worth.…”
Section: Discussionmentioning
confidence: 99%
“…Before we examine the validity of this developmental model, it is important to note the lack of semantic clarity in much of the literature around the use of such terms as moral identity, the moral self, moral self‐identity , and moral selfhood . Although some scholars make a clear distinction between the terms moral self and moral identity to distinguish between what they regard as dissimilar psychological constructs pertinent to disparate developmental periods, others use the terms moral identity, the moral self, moral self‐identity , and moral selfhood interchangeably when referring exclusively to its mature form in adolescence and adulthood (see, e.g., Aquino & Reed, ; Frimer & Walker, ; Hardy & Carlo, ; Harkrider et al ., ; Jordan, Mullen, & Murnighan, ). Others employ the term moral self when referring to both the mature adult form of this construct and its purported developmental antecedent in early childhood (see, e.g., Krettenauer, ).…”
Section: Introductionmentioning
confidence: 99%
“…We add to that work by examining the consequences of UPB through the new lens of cognitive dissonance theory; we find that to reduce dissonance after engaging in UPB, employees downgrade the importance of moral characteristics in their self-conception, which in turn leads to less ethical behaviors (i.e., OCB) and more unethical behaviors (i.e., CWB) in the workplace. These findings suggest that the aftermath of UPB requires special attention because UPB can lead to subsequent undesirable behaviors that may disturb organizational functioning (Chen et al, 2016;Harkrider et al, 2013). Second, our study broadens the application of cognitive dissonance theory in behavioral ethics literature by capturing moral identity internalization as a cognitive approach to reduce cognitive dissonance due to UPB.…”
Section: Theoretical Contributionsmentioning
confidence: 78%